Ethical Musicality - Trondalen, Gro (Routledge Research in International Law, 2023)
Ethical Musicality addresses the crossroads between music and ethics, combining philosophical knowledge, theoretical reflection, and practical understanding. When tied together, music and ethics link profoundly, offering real-life perspectives that would otherwise be inaccessible to us. The first part elucidates music and ethics through some influential and selected scholars ranging from Antiquity via modern philosophy to contemporary voices. In the second part, different roles and arenas are illustrated and explored through various music practices in real-life encounters for the musician, the music educator, the music therapist, the musicologist, the 'lay' musician, and the music researcher. The third part unfolds an ethical musicality focusing on the body, relationship, time, and space. Following these fundamental existentials, ethical musicality expands our lifeworld, including context, involvement, power, responsibility, sustainability, and hope. Such an ethical musicality meets us with a calling to humanity - offering hope of a 'good life'.